2009
DOI: 10.1080/14697680802595643
|View full text |Cite
|
Sign up to set email alerts
|

Does beta react to market conditions? Estimates of ‘bull’ and ‘bear’ betas using a nonlinear market model with an endogenous threshold parameter

Abstract: We apply a logistic smooth transition market model (LSTM) to a sample of returns on Australian industry portfolios to investigate whether bull and bear market betas differ. Unlike other studies, our LSTM model allows for smooth transition between bull and bear states and allows the data to determine the threshold value. The estimated value of the smoothness parameter was very large for all industries implying that transition is abrupt. Therefore we estimated the threshold as a parameter along with the two beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…However, recent empirical studies develop and apply such models to the risk premiums of stocks. For example, Chen, Lin, and Yu () and Woodward and Anderson () apply threshold‐type CAPM frameworks to investigate regime‐switching in stock returns, particularly driven by time‐varying β s. Gulen, Xing, and Zhang () and Ozoguz () utilize two‐state Markov‐switching models to investigate CRSP value‐weighted portfolios. Their frameworks assume that the same unobserved state variable governs risk‐adjusted stock returns ( α ), the volatility of excess returns, and the factor coefficients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, recent empirical studies develop and apply such models to the risk premiums of stocks. For example, Chen, Lin, and Yu () and Woodward and Anderson () apply threshold‐type CAPM frameworks to investigate regime‐switching in stock returns, particularly driven by time‐varying β s. Gulen, Xing, and Zhang () and Ozoguz () utilize two‐state Markov‐switching models to investigate CRSP value‐weighted portfolios. Their frameworks assume that the same unobserved state variable governs risk‐adjusted stock returns ( α ), the volatility of excess returns, and the factor coefficients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In down market, prices are failing and going down, which shows a lack of confidence. Recently, Mitchell and Pulvino () and Woodward and Anderson () ended with the same conclusion that there is a correlation between the security's Beta and the market states.…”
Section: Random Betamentioning
confidence: 99%
“…Clinebell et al (1993) show that observed differences of beta coefficients between "bull" and "bear" market conditions are significant. More recently, Woodward and Anderson (2009) applying a logistic smooth transition market model for Australian industry portfolios report that "bull" and "bear" betas are significantly different for most industries while the transition between "bull" and "bear" states is rather abrupt. The variation on asset returns (Rosenberg and Guy, 1976a, b;Bos and Newbold, 1984) has been attributed to the influence of microeconomic factors such as operational changes in the company or macroeconomic factors such as the rate of inflation and expectations about relevant future events.…”
Section: Introductionmentioning
confidence: 99%